PENYEHATAN PERILAKU BULLYING PADA KAUM SANTRI DI “PESANTREN MINORITAS” TANAH TORAJA SULAWESI SELATAN - Rahmatullah, Azam Syukur; M. Suud, Fitriah; Azis, Nurlinda (IAIN Ponorogo, 2022)
This study investigates bullying done by santri (Islamic boarding school students), which happens in any Islamic boarding school, whether large or small, majority or minority, salafiyah or khalafiyah Islamic boarding schools. As happened in the minority Islamic boarding school in Tana Toraja, South Sulawesi, there are indications of bullying by fellow santri. However, the levels in each Islamic boarding school are different. Hence, this study used an ethnomethodological approach to observing individual behavior by taking conscious actions, how they acted, or how they learned in taking these actions. The data were collected through an in-depth interview with the research respondents. Data description and interpretation were carried out since the data collection earlier using the ethnomethodological approach. It did not wait for the data to accumulate a lot. The study results showed that although Islamic boarding school was a minority, it was not necessarily free from the behavior of santri who were bullying other santri. Santri, who did the bullying, resulted from the parents’ formation and unfriendly upbringing while at home, negatively impacting other santri. Meanwhile, the healing of bullying conducted by the Islamic boarding school focused on healing the soul and heart by strengthening the spiritual aspect so that there is a unification of feelings between santri and God.